Protocol of a multi-centre randomized controlled trial to compare pericapsular nerve group block, fascia-iliaca compartment block and femoral nerve block for pain management in patients with a hip fracture in the emergency department (CPFF-ED) - Jurian Dolstra; Svenja L. Haak; E. Christiaan Boerma; Heleen Lameijer; Ewoud Ter Avest (PLoS ONE, 2026)
Background Patients presenting in the emergency department (ED) with a hip fracture are often in significant pain. Opioids are frequently prescribed as part of standardized pain protocols, but are associated with many adverse events, especially in the elderly. Regional anaesthesia with a femoral nerve block (FNB), Fascia Iliaca compartment block (FICB) or Pericapsular nerve block (PENG) may provide a reasonable alternative to these patients. We designed a prospective multicentre study to compare the efficacy and safety of these blocks in the ED setting, which has been registered in the Centrale Commissie Mensgebonden Onderzoek (CCMO) Research Portal (NL-OMON57433). Methods and analysis A multicentre Randomized Controlled Trial (RCT), conducted in the ED of 5 hospitals in the Netherlands. A total of 254 adult patients (18+) presenting to the ED with a neck of femur or pertrochanteric femur fracture will be randomised to receive FNB, FICB or PENG in the ED after informed consent has been obtained. Patients will be followed for 12 hours after block placement in the ED. The primary (patient reported) outcome measure is overall patient wellbeing 6–8 hours after block administration (or until operation, whichever comes first) as scored by the validated Quality of Recovery (QoR-15) questionnaire. Secondary outcome measures will be pre-operative pain scores, the cumulative dose of analgesics used during the first 12 hours after block placement or until operation, and complication rates for each of the blocks. Expected results This randomized controlled trial with a superiority design will allow conclusions on which regional nerve block is most effective in improving pre-operative wellbeing in patients with a neck of femur or pertrochanteric fracture. The choice to use a patient reported outcome measure to evaluate block efficacy maximizes clinical relevance. And by allowing the choice of local anaesthetic to the participating hospital (with a 1:1:1 randomization for each participating centre) clinical applicability of our findings is maximized.